1994
DOI: 10.1002/hep.1840190512
|View full text |Cite
|
Sign up to set email alerts
|

The canadian multicenter double-blind randomized controlled trial of ursodeoxycholic acid in primary biliary cirrhosis

Abstract: Ursodeoxycholic acid, a dihydroxyl bile acid normally present in human beings in minimal amounts, becomes incorporated into the bile salt pool when taken orally. In cholestasis, bile acids are retained in the liver and are hepatotoxic. Ursodeoxycholic acid is the least-known hepatotoxic bile acid, has choleretic properties and is reported to benefit patients with chronic cholestasis. In a nationwide Canadian controlled trial, 222 patients with primary biliary cirrhosis were treated with ursodeoxycholic acid (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
218
1
14

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 390 publications
(240 citation statements)
references
References 33 publications
7
218
1
14
Order By: Relevance
“…On the other hand, some studies have reported that UDCA decreases gallbladder contractility. 19 Heathcote et al 20 reported that, after UDCA administration, fasting gallbladder volumes were greater, and percentages of gallbladder emptying were decreased compared with those in untreated gallstone patients.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, some studies have reported that UDCA decreases gallbladder contractility. 19 Heathcote et al 20 reported that, after UDCA administration, fasting gallbladder volumes were greater, and percentages of gallbladder emptying were decreased compared with those in untreated gallstone patients.…”
Section: Discussionmentioning
confidence: 97%
“…Tab. 3) und der Transplantationsindikation [9] sowie bei frühzeitigem Therapiebeginn zu einer signifikanten Lebensverlängerung [19,32]. [23] 55 Gebessert Unverändert Fraglich Poupon et al 1991Poupon et al ,1994 146 Gebessert Gebessert Gebessert Lindor et al 1994Lindor et al , 1996 178 Gebessert Gebessert Unverändert Heathcote et al 1994 [9] 222 Gebessert Gebessert Gebessert Turner et al 1994 [35] 46 Gebessert Gebessert n. s. Combes et al 1995 [5] 149 Gebessert Gebessert Gebessert [20] 105 Gebessert Gebessert Unverändert Mitchell et al 1997 [22] 24 Gebessert Gebessert Gebessert…”
Section: Zytoprotektion Durch Gallensäurenunclassified
“…Eine kombinierte Analyse von drei großen Studien (276 Patienten mit UDCAMonotherapie gegenüber 277 Patienten mit Plazebo über 4 bzw. 3,8 Jahre) zeigte weiterhin eine 32%ige Risikominimierung (± 11%), zu versterben oder sich einer Lebertransplantation unterziehen zu müssen [31]. Dennoch sind die Daten bezüglich durch UDCA bedingter histologischer Verbesserung kontrovers: Einige Studien haben keine histologische Verbesserung gezeigt [54], andere haben über eine geringere portale und lobuläre Entzündung, weniger Nekrosen und Cholestase berichtet [22,31,70].…”
Section: Primär-biliäre Zirrhoseunclassified
“…3,8 Jahre) zeigte weiterhin eine 32%ige Risikominimierung (± 11%), zu versterben oder sich einer Lebertransplantation unterziehen zu müssen [31]. Dennoch sind die Daten bezüglich durch UDCA bedingter histologischer Verbesserung kontrovers: Einige Studien haben keine histologische Verbesserung gezeigt [54], andere haben über eine geringere portale und lobuläre Entzündung, weniger Nekrosen und Cholestase berichtet [22,31,70]. Die UDCA verlangsamt die Krankheitsprogression der primär-biliären Zirrhose und vermindert die Notwendigkeit für eine orthotope Lebertransplantation [55,71,72].…”
Section: Primär-biliäre Zirrhoseunclassified
See 1 more Smart Citation